Analysis of the Influence of Marketing Mix 4P on Purchase and Repurchase Decisions Using SEM Tools (Case Study on Nugget Fiesta Consumers in Surabaya) - Caesarika, Mechtildis Vanessa; Safirin, Mochamad Tutuk (Universitas KH. Abdul Chalim Mojokerto, 2025)
Competition ina thea instant food industry, especially processed products such as nuggets, is increasing along with the public's need for practical food. One of the nugget brands, Fiesta, experienced a decline in ranking in the Top Brand Index from 2022-2024, so an evaluation is needed through thea 4P marketinga mixa approach, namely product, price, place, and promotion. The method used is quantitative with data collection through questionnaires from 130 respondents in Surabaya and analyzed using Structural Equation Modeling (SEM)-AMOS. The results show that the product, price and promotion hasa aa significanta effecta ona purchasinga decisions, place do not havea aa significanta effecta ona purchasinga decisions, product and price has a significant effect on repeat purchases, place anda promotion do not havea a significant effecta ona repeat purchases, anda purchasinga decisionsa havea aa significanta effect ona repeat purchases.